2017
DOI: 10.1097/sla.0000000000001527
|View full text |Cite
|
Sign up to set email alerts
|

Curative Surgical Resection of Adrenocortical Carcinoma

Abstract: Objective To evaluate conditional disease-free survival (CDFS) for patients who underwent curative intent surgery for adrenocortical carcinoma (ACC). Background ACC is a rare but aggressive tumor. Survival estimates are usually reported as survival from the time of surgery. CDFS estimates may be more clinically relevant by accounting for the changing likelihood of disease-free survival (DFS) according to time elapsed after surgery. Methods CDFS was assessed using a multi-institutional cohort of patients. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 42 publications
1
13
0
2
Order By: Relevance
“…Compared with cumulative survival, CS could reflect changes in survival probability due to prolonged survival, and is more useful for predicting prognosis 19 - 21 . Donald et al have reported the conditional survival of patients with different stages of breast cancer between 1983 and 1987 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Compared with cumulative survival, CS could reflect changes in survival probability due to prolonged survival, and is more useful for predicting prognosis 19 - 21 . Donald et al have reported the conditional survival of patients with different stages of breast cancer between 1983 and 1987 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-five studies reporting on risk factors for recurrence and/or mortality, and that included more than 100 patients with histologically proven ACC, were analyzed (1,8,20,25,26,29,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82) (see Appendix 2 for details of studies included, and Appendix 3 for an overview of all prognostic factors studied). The threshold of 100 cases was defined upfront as with n = 100 and an expected number of deaths of 50, statistical power was considered sufficient.…”
Section: Clinical Question 2: Prognostic Factorsmentioning
confidence: 99%
“…Larger C-index and AUC value show higher ability to distinguish patients from different survival outcomes. Last, Kaplan-Meier curves were plotted over patients grouped by risks predicted from the nomogram to further assess calibration [18]. A two tailed p<0.05 was considered statistically significant.…”
Section: Discussionmentioning
confidence: 99%